Meshed Acellular Dermal Matrix in Immediate Prepectoral Implant-based Breast Reconstruction. Issue 11 (November 2020) - Scheflan, Michael; Allweis, Tanir M.; Ben Yehuda, Dafna; Maisel Lotan, Adi
Abstract : Background: Prepectoral implant placement has many potential advantages in immediate breast reconstruction. Acellular dermal matrices (ADMs) are commonly used in these surgeries. ADM meshing may enhance integration, decrease seroma and infection rates, and reduce surgical costs. Methods: This was a retrospective, single-center study of 49 women (71 breasts) undergoing immediate, prepectoral, implant-based breast reconstruction with 2:1 meshed, bovine-derived ADM (SurgiMend). Outcomes were compared against those of 77 patients (105 breasts) undergoing a similar procedure but with partial subpectoral implant placement. Results: In the prepectoral group, the mean age was 49.1 years and mean body mass index was 24.7 kg/m 2 . There were no significant differences in baseline characteristics versus the partial subpectoral control group. Mean follow-up was 18.6 months (prepectoral) and 21.3 months (partial subpectoral). Mean time to drain removal was reduced in the prepectoral group (6.5 versus 8.5 days; P < 0.001). Rates of minor and major complications with prepectoral implant placement were 15.5% and 11.3%, respectively – similar to partial subpectoral placement (15.2% and 14.3%) (overall P = 0.690). Capsular contracture and explantation were associated with radiation therapy, and rates were similar between groups. Conclusions: Prepectoral implant placement with meshed ADM is a safe and reproducible alternative to partial muscle coverage with meshed ADM. Recovery may be easier and animation deformity avoided. It could therefore become the standard of care for implant-based breast reconstruction.